Pengaruh Media Pendingin Bio Solar Pada Perlakuan Panas Untuk Meningkatkan Kekerasan Roda Gigi Sproket - Gusmantoro, Devri; Erwansyah, Erwansyah; Dwi Krishnaningsih, Shanty (Jurnal Inovasi Teknologi Terapan, 2023)
The sprocket gears is one part of motorcycle that functions as a power transfer transmission. The service of gears can be influenced by several aspect, one of which is the hardness of sprocket gears. The hardness of the sprocket gear material can be increased by various mathod, one of which is heat treatment. This study used an experimental method with the aim of knowing the effect of bio diesel as the main cooling medium on increasing the hardness of non-original sprocket gears. The research process included carburizing and hardening processes on 2 non-original brands at temperature of 910°C and then cooled using bio diesel and water cooling media with a holding time of 30 minute and 60 minutes. The results showed that the heat treatment process could increase the hardness of brand A with a normal hardness of 104 HB resulting in the highest value in the parameter holding time of 60 minute and water cooling medium with a hardness value of 111,6 HB and brand B of normal hardness with a value of 110,8 HB producing the highest value is the holding time parameter of 60 minutes and water cooling medium with a hardness value of 115,9 HB. Based on the result obtained, water cooling medium is higher than bio diesel cooling medium.